Evaluation of the navigation effectiveness of an organizational taxonomy built on a general classification scheme and domain thesauri. (7th January 2014) - Wang, Zhonghong; Khoo, Christopher S.G.; Chaudhry, Abdus Sattar
<x xml:space="preserve">Abstract</x> This paper presents an evaluation study of the navigation effectiveness of a multifaceted organizational taxonomy that was built on the Dewey Decimal Classification and several domain thesauri in the area of library and information science education. The objective of the evaluation was to detect deficiencies in the taxonomy and to infer problems of applied construction steps from users' navigation difficulties. The evaluation approach included scenario‐based navigation exercises and postexercise interviews. Navigation exercise errors and underlying reasons were analyzed in relation to specific components of the taxonomy and applied construction steps. Guidelines for the construction of the hierarchical structure and categories of an organizational taxonomy using existing general classification schemes and domain thesauri were derived from the evaluation results.